The bed book of short stories - Kubuitsile, Lauri; Hichens, Joanne (Modjajj Books, 2010)
The bed, dressed in hand sewn quilt or threadbare blanket, may in and of itself be memorable, but it is what happens in the bed - the sex and lovemaking, the dreams, the reading, the nightmares, the rest, giving birth and dying - which give "bed" special meaning. Whether a bed is shared with a book, a child, a pet or a partner, whether lovers lie in ecstasy or indifference, whether "bed" relates to intimacy or betrayal, it is memories and recollections of "bed", in whatever form, which have triggered the writing of these thirty stories by women from southern Africa. Well known writers Joanne Fedler, Sarah Lotz, Arja Salafranca, Rosemund Handler and Liesl Jobson will delight, but you will discover here new writers from Botswana, Zimbabwe, Mozambique, Malawi, Namibia and Zambia, each with a unique voice as they cast light on the intimate lives of women living in this part of the world and the possibilities that are both available to and denied them. The Bed Book of Short Stories - some quirky and tender, others traumatic or macabre - is the perfect companion to take to bed with you, to keep you reading long into the night.